PENGARUH SISTEM SELEKSI, PELATIHAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT.X - Liyanwah Liyanwah; Ian Nurpatria Suryawan (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This study aims to determine the effect of selection system, traning and job satisfication on employee performance of PT. X. This studi uses non-probability sampling techiques with sampling jenuh method and amounted to 61 respndents. The technique of collecting data through a interview, and quesionnaire with a likert scale. the results of this study show that selection system, training and job satisfication influential with employee performance.